Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae) - Littmann, Michael W. (Zootaxa, 2007)
The genus Sorubim Cuvier, 1829, and two species, S. lima (Bloch & Schneider 1801) and S. trigonocephalus Miranda- Ribeiro, 1920, are redescribed based on the examination of type material and about 400 non-type specimens from ichthyological collections in Europe and North and South America. The five species of the genus are, in addition to S. lima and S. trigonocephalus, S. elongatus Littmann, Burr, Schmidt and Isern 2001, found in the Essequibo, Orinoco, and Amazon basins; S. cuspicaudus Littmann, Burr and Nass 2000, occurring in the Sinu, Cauca, and Magdalena rivers of Colombia and the Lago Maracaibo basin of Colombia and Venezuela; and S. maniradii Littmann, Burr and Buitrago-Suarez 2001, known from the upper and middle Amazon basin. Sorubim lima is the widest-ranging species, occurring in most of the major drainage basins of South America. Sorubim trigonocephalus is extremely rare in natural history collections and is currently known from only two major tributaries of the Amazon basin. Three species (S. maniradii, S. elongatus, and S. lima) occur syntopically. Species of Sorubim are diagnosed on the basis of body and head shape, differences in fin ray and gill-raker numbers, mental barbel position, and degree of pigmentation of the lateral stripe. At least two of the species (S. lima and S elongatus) make up part of the ornamental fish trade and are sold for food in local fish markets in South America. A key to adults of the five species is included.